Optimization for Wireless Powered Communication Networks - Gui, Guan; Lyu, Bin (SpringerBriefs in Electrical and Computer Engineering, 2019)
This SpringerBrief introduces the basics of wireless powered communication networks (WPCNs). In particular, the background and concept of WPCNs are briefly discussed. Moreover, this brief provides an extensive study of the recent developments in this area from an optimization perspective. Wireless powered communication network (WPCN) is a new network paradigm for IoT, where wireless devices (WDs) are powered by radio frequency (RF) based wireless power transfer (WPT) to eliminate the need for recharging or replacing the batteries manually and to prolong their lifetime.In this context, the brief also discusses some optimization problems for state-of-the-art scenarios of wireless powered communication networks. The target audiences for this SpringerBrief are researchers, engineers, and undergraduate and graduate-level students, who are studying or working in wireless powered communication networks and its performance optimization.